WISATA RELIGI DI BALI: - Muhamad Murtadho (Jurnal Dialog, 2015)
Religious tourism serves as an attractive choice in revitalizing religious faith among people in the modern society and an economic improvement for the local society. Bali as one of world-class tourist attractions in Indonesia has been known as the land of god that indicates its religiousness. This study attempts to explore the potential of religious tourism in Bali from the perspectives of non –Hindu people. Focusing on the potentials of Islamic tourism in Bali, this study finds out that there is a high potential for non-Hindu tourism in Bali and that there is a demand for non-Hindu-friendly tourism including the availability of halal foods and decent praying facilities.